Pemanfaatan Limbah Jagung dan Kedelai untuk Pakan Ternak Ruminansia di Desa Jatiwates Kecamatan Tembelang Jombang - Ambar Susanti; Primaadi Airlangga; M Irfan Fauzi; Faruq Hidayatullah; Siti Naimah (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2022)
The implementation of community service using agricultural biomass through the Utilization of Corn and Soybeans’straw using the fermentation method for ruminant livestock feed, was carried out in Jatiwates Village, Tembelang District, Jombang. The activity will be carried out in October 2021. The objectives of the implementation of community service are; 1) introduce about the use of agricultural production waste as raw material for ruminants using the fermentation method, and 2) grow the interest of farmers and ranchers to develop the potential of agricultural production waste in their environment to be economical and environmentally friendly. The target audience who participates in community service are farmers who are members of the Jatiwates Village group, and some of them are also ruminant breeders. Steps The activities carried out consist of 1) Observation, 2) lecture, 3) practice/training, and 4 ) evaluation. The implementation of community service by the Unwaha Team regarding the Utilization of Corn and Soybean’s straw as raw materials for ruminant animal feed in Jatiwates Village, Tembelang District, Jombang, obtained quite good results. Agricultural waste treatment using the fermentation method needs to be socialized to the public. The hope for this activity is that the community will be more aware of the opportunities for utilizing agricultural waste among the community to be useful and have economic potential